2016
DOI: 10.1016/j.jpedsurg.2016.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric inguinal and scrotal surgery — Practice patterns in U.S. academic centers

Abstract: Purpose Both pediatric urologists and pediatric surgeons perform hernia repairs, hydrocelectomies and orchiopexies. We hypothesized that surgeons perform more incarcerated and female hernia repairs while urologists perform more orchiopexies and hydrocelectomies. Methods The Vizient-AAMC Faculty Practice Solutions Center® database was queried from January 2009 to December 2014 to identify patients 10 years or younger who underwent the above procedures performed by pediatric specialists. Age, gender, race, ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 21 publications
1
13
0
1
Order By: Relevance
“…Previous attempts to understand practice patterns between pediatric urologists and pediatric surgeons for management of UDT suggest that, when patients are referred to pediatric urologists in US academic centres, the age at referral and volume are higher compared to referrals to pediatric surgeons. 14,16 These results are consistent with our findings. However, we examined practice patterns among 2 groups of surgeons who practise in a single-payer, open-access system where UDT is managed by both specialist groups.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Previous attempts to understand practice patterns between pediatric urologists and pediatric surgeons for management of UDT suggest that, when patients are referred to pediatric urologists in US academic centres, the age at referral and volume are higher compared to referrals to pediatric surgeons. 14,16 These results are consistent with our findings. However, we examined practice patterns among 2 groups of surgeons who practise in a single-payer, open-access system where UDT is managed by both specialist groups.…”
Section: Discussionsupporting
confidence: 93%
“…19 Previous investigations of age of patients with UDT in other countries including the US, Australia and Germany showed that many boys older than the age recommended by guidelines were referred for surgery. 20,16,21 A recent study in Australia indicated that there may be a second peak of UDT in boys aged 5-9 years owing to retractile testes that have developed into acquired or secondary ascended testes. 21 Therefore, the observations from the current study may not truly reflect the age at referral for all primary congenital UDTs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The numbers of children who need specialized surgery are greater than the health system is capable of attending. Consequently, children have been operated by other specialties, such as urology [3]. This is brought about by negligence in essential aspects of child surgery that should be based on clinical evidence and the effective costs of the treatment, aiming at providing benefits to an escalating number of children [12].…”
Section: Discussionmentioning
confidence: 99%
“…A significant group of children have been operated by other specialties, such as urology, whereas pediatric surgeons are usually engaged in the correction of hernias (primary and recurrent), corrections using laparoscope in younger children and girls. On the other hand, pediatric urologists operate most frequently hydrocelectomies (62%), orchiopexies (83%) [3].…”
Section: Introductionmentioning
confidence: 99%